More Than 500 Kids Could Be Saved Each Year! Ten Consensus Actions to Improve Quality of Pediatric Resuscitation in DACH-Countries (Austria, Germany, and Switzerland) - Jung, Philipp; Brenner, Sebastian; Bachmann, Iris; Both, Christian; Cardona, Francesco; Dohna-Schwake, Christian; Eich, Christoph; Eifinger, Frank; Huth, Ralf; Heimberg, Ellen; Landsleitner, Bernd; Olivieri, Martin; et al. (Frontiers in Pediatrics, 2020)
• Quality and outcome of pediatric resuscitation often does not achieve recommended goals. • Quality improvement initiatives with the aim of better survival rates and decreased morbidity of resuscitated children are urgently needed. • These initiatives should include an action framework for a comprehensive, fundamental and interprofessional reorientation of clinical and organisational structures concerning resuscitation and post resuscitation care of children. • The authors of this DACH position statement suggest the implementation of ten evidence-based actions (for out-of-hospital and in-house cardiac arrests) that should improve survival rates and decrease morbidity of resuscitated children with better neurological outcome and quality of life.